Two new species of ground-dwelling Cyrtodactylus (Geckoella) from the Mysore Plateau, south India - Agarwal, Ishan (Zootaxa, 2016)
Two new species of ground-dwelling geckos of the genus Cyrtodactylus (Geckoella) are described from the Mysore Plateau, in southern India. The new species are members of the C. collegalensis species complex, with 8.7 % uncorrected ND2 sequence divergence from each other and greater than 10 % divergence from described members of the C. collegalensis complex, from which they differ in subtle aspects of colour pattern and morphometric ratios. The type localities of the new species are ~ 130 km apart, and 100 km and 225 km from the type locality of C. collegalensis in the Biligiriranga Hills. The discovery of these new species in isolated mountains within a small area suggests other high elevation areas in the region may have undescribed species, and a redefinition of biodiversity patterns in peninsular India.